The Role of Law in the Formation of the Modern World Multipolarity: Review of the Faculty of Law Section of the North-Western Institute of the Management of the RANEPA in the framework of the VII International Neva Forum - N. V. Razuvaev; I. K. Shmarko (Теоретическая и прикладная юриспруденция)
This article provides a review of the meeting of the Section of the Law Faculty of the North-Western Institute for the Directorate of the RANEPA as part of the VII International Neva Forum. It was devoted to the role of law in the formation of a multipolar world in modern geopolitical conditions.